Perencanaan Dan Perancangan Pusat Industri Dan Workshop Gerabah Di Desa Kapal, Kecamatan Mengwi - I Gusti Ayu Sri Utari Dewi Dewi; I Nyoman Gede Maha Putra; Gde Bagus Andhika Wicaksana (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Pottery is a piece of ceramic made of clay. Objects from this pottery have many uses such as religious ceremony facilities, household items, and decorative objects. The interest of the younger generation to continue this business continues to decline. This study discusses the planning and design of an industrial center and pottery workshop located in Kapal village, Mengwi sub-district so that it can help preserve and introduce the pottery culture that has existed since the time of the ancestors, to be precise around 1,500 BC. Based on the existing problems, there are no training places regarding the development of pottery production, the unavailability of an exhibition space that can function to display the work of clay craftsmen so that the younger generation or tourists are interested in pottery crafts. for people who want to know and want to learn firsthand about pottery making so that pottery products can develop and have new innovations. This proposal is balanced with a strategy in the form of an architectural ecology approach. Through an architectural ecology approach, it is hoped that the building can provide harmony between nature and humans in a reciprocal relationship. The results showed that the existence of an industrial center and pottery workshop designed with an approach strategy that can help attract the interest of the younger generation and craftsmen can also give birth to a new innovation that is able to solve problems regarding the pottery industry in Kapal Village, Mengwi District with targeted facilities.